Global studies : - Goldman, Minton F. (McGraw - Hill, 2005)
This tenth edition of Global Studies: Russia, The Eurasian Republics, and Central/Eastern Europe continues to provide introductory essays, up-to-date background information, and current statistics on the region. A collection of world press articles, topically arranged, complements the background information.